Isolation of chemical constituents from Alphonsea sp and their in silico xanthine oxidase inhibitory activities - M. Nur Sidik (Tanjong Malim, 2022)
Isolation of chemical constituents from Alphonsea sp and their in silico xanthine oxidase inhibitory activities by M. Nur Sidik